2010
DOI: 10.1245/s10434-010-1032-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Low Molecular Weight Heparin Thromboprophylaxis on Bleeding Complications After Gastric Cancer Surgery

Abstract: LMWH thromboprophylaxis was found to increase significantly the risk of bleeding complications after gastric cancer surgery. Optimal LMWH prophylaxis regimens, including the dosage and timing of treatment commencement, for gastric cancer surgery should be determined in further clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 23 publications
3
35
2
Order By: Relevance
“…Relatively little research has attempted to identify risk factors for thromboprophylaxis-related bleeding in general or abdominal-pelvic surgery, although a few studies have identifi ed risk factors in patients undergoing gastric cancer surgery, 85 pancreaticoduodenectomy, 86 partial hepatic resection, 87 and mixed abdominal surgery ( Table 8 ). 88 In the absence of data from large, prospective, population-based observational studies, the baseline risk of bleeding can be derived from the control (placebo or no pharmacologic prophylaxis) groups in randomized trials.…”
Section: Baseline Risk Risk Factors and Risk Stratifi Cation For Mamentioning
confidence: 99%
“…Relatively little research has attempted to identify risk factors for thromboprophylaxis-related bleeding in general or abdominal-pelvic surgery, although a few studies have identifi ed risk factors in patients undergoing gastric cancer surgery, 85 pancreaticoduodenectomy, 86 partial hepatic resection, 87 and mixed abdominal surgery ( Table 8 ). 88 In the absence of data from large, prospective, population-based observational studies, the baseline risk of bleeding can be derived from the control (placebo or no pharmacologic prophylaxis) groups in randomized trials.…”
Section: Baseline Risk Risk Factors and Risk Stratifi Cation For Mamentioning
confidence: 99%
“…However, it is possible that pharmacological prophylaxis may induce major bleeding complications as one of the adverse events of anticoagulant medication [22]. Garry et al [23] showed Fig.…”
Section: Discussionmentioning
confidence: 99%
“…There were no thromboembolic events or epidural hematomas in either of our groups, and there was no postoperative bleeding associated with thromboprophylaxis. Jeong et al [22] reported that perioperative low-molecular-weight heparin as thromboprophylaxis significantly increased the risk of bleeding after gastric surgery. Therefore, an optimal thromboprophylaxis regimen of should be determined in further trials.…”
Section: Discussionmentioning
confidence: 99%